3(a+14)=6(2a+3)

Simple and best practice solution for 3(a+14)=6(2a+3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(a+14)=6(2a+3) equation:


Simplifying
3(a + 14) = 6(2a + 3)

Reorder the terms:
3(14 + a) = 6(2a + 3)
(14 * 3 + a * 3) = 6(2a + 3)
(42 + 3a) = 6(2a + 3)

Reorder the terms:
42 + 3a = 6(3 + 2a)
42 + 3a = (3 * 6 + 2a * 6)
42 + 3a = (18 + 12a)

Solving
42 + 3a = 18 + 12a

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-12a' to each side of the equation.
42 + 3a + -12a = 18 + 12a + -12a

Combine like terms: 3a + -12a = -9a
42 + -9a = 18 + 12a + -12a

Combine like terms: 12a + -12a = 0
42 + -9a = 18 + 0
42 + -9a = 18

Add '-42' to each side of the equation.
42 + -42 + -9a = 18 + -42

Combine like terms: 42 + -42 = 0
0 + -9a = 18 + -42
-9a = 18 + -42

Combine like terms: 18 + -42 = -24
-9a = -24

Divide each side by '-9'.
a = 2.666666667

Simplifying
a = 2.666666667

See similar equations:

| -19=-3+4w | | 6x-2k+8=x+5 | | 8n^2=6 | | 294=18-y | | 35y^2-9y+3=0 | | 284=18-y | | 2m^2+27m-4=0 | | 2n+3=4n-7 | | 1.75x=4.2 | | 6n+12=20 | | 2m^2=10-2m | | (n+3)(2n+3)=0 | | 10+9x=10+x | | x^2+y^2+2*x+14*y-15=0 | | 2n^2=105-11n | | 10x-17=2x+10 | | 5.7-6/12 | | x(a-6b)=3m(x-c) | | 0=-16t+40t-84 | | 26-m=76 | | g(x)=x^5-9x^3 | | 6(15-3x)=120 | | -3(x+5)=-30 | | y=4(a)+3+2 | | 8(2+x)=80 | | 12321+231756= | | 2(5x-3)=74 | | -8a-(7b)= | | 6+50=-12 | | 5(x+9)=50 | | 6a+7=18 | | 100=(0.2)2/2 |

Equations solver categories